Impact of selected cement additives and model compounds on the solubility of Nd(III), Th(IV) and U(VI): screening experiments in alkaline NaCl, MgCl2 and CaCl2 solutions at elevated ionic strength - Adam, Nicole; Hinz, Katja; Gaona, Xavier; Panak, Petra J.; Altmaier, Marcus (Radiochimica acta, 2021)
The solubility of Nd(III), Th(IV) and U(VI) was studied from undersaturation conditions in the presence of selected organic cement additives and model compounds: adipic acid, methyl acrylate, citric acid, melamine, ethylene glycol, phthalic acid and gluconic acid. Experiments were performed under Ar atmosphere in NaCl (2.5 and 5.0 M), MgCl2 (1.0 and 3.5 M) and CaCl2 (1.0 and 3.5 M) solutions with 9 <= pH(m) <= 13 (pH(m) = -log[H+]). Initial concentrations of organic ligands in solution were set constant in all systems to [L](0) = 0.025 M, except in specific cases (e.g. adipic acid, melamine and phthalic acid) where the ligand concentration in the matrix solutions was lower and controlled by solubility. Adipic acid, methyl acrylate, melamine, ethylene glycol and phthalic acid do not impact the solubility of Nd(III), Th(IV) and U(VI) in the investigated NaCl, MgCl2 and CaCl2 systems. Citrate significantly enhances the solubility of Nd(III), Th(IV) and U(VI) in NaCl systems. A similar effect was observed for Th(IV) and U(VI) in the presence of gluconate in NaCl systems. The impact of pH on the stability of the complexes is different for both ligands. Because of the larger number of alcohol groups in the gluconate molecule, this ligand is prone to form more stable complexes under hyperalkaline conditions that likely involve the deprotonation of several alcohol groups. The complexation of gluconate with U(VI) at pH(m) approximate to 13 is however weaker than at pH(m) approximate to 9 due to the competition with the highly hydrolysed moiety prevailing at pH(m) approximate to 13, i.e. UO2(OH)(4)(2-). The impact of citrate and gluconate in MgCl2 and CaCl2 systems is generally weaker than in NaCl systems, expectedly due to the competition with binary Mg-L and Ca-L complexes. However, the possible formation of ternary complexes further enhancing the solubility is hinted for the systems Mg/Ca-Th(IV)-GLU and Ca-U(VI)GLU. These observations reflect again the differences in the complexation properties of citrate and gluconate, the key role of the alcohol groups present in the latter ligand, and the importances of interacting matrix cations. The screening experiments conducted within this study contribute to the identification of organic cement additives and model compounds potentially impacting the solution chemistry of An(III)/Ln(III), An(IV) and An(VI) under intermediate to high ionic strength conditions (2.5 <= I <= 10.5 M). This shows evident differences with respect to investigations conducted in dilute systems, and thus represents a very relevant input in the safety assessment of repositories for radioactive waste disposal where such elevated ionic strength conditions are expected.
Gesehen am 12.08.2021
Im Text ist "2" tiefgestellt